If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(7y + x) = 6 Reorder the terms: 5(x + 7y) = 6 (x * 5 + 7y * 5) = 6 (5x + 35y) = 6 Solving 5x + 35y = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-35y' to each side of the equation. 5x + 35y + -35y = 6 + -35y Combine like terms: 35y + -35y = 0 5x + 0 = 6 + -35y 5x = 6 + -35y Divide each side by '5'. x = 1.2 + -7y Simplifying x = 1.2 + -7y
| 4c-6-(c+7)= | | 11z+5=2(4z-5) | | 5-4.9a=39.2 | | 3w^2+16w=864 | | 27-5x=-44-9x | | 20=5w-w | | 277+96+277(0.01083032491+-1y)+277y=376 | | 54=2x+4x | | 3(4-2x)=-9 | | Cos(3.1416/6) | | W(20)=13.2x+443 | | 4r-7+6r=19 | | 17=8t-36 | | Y=2x^2+12x-91 | | 7y=5-12 | | 3x^2+16-5=0 | | x/4-1/6≤12 | | -12=.2/f | | 277+96+277x+277y=376 | | 4xy-5x+4y^3=-40 | | 4(5x-4(5x+y))= | | Y=2.3x+0.2 | | 171=3x+2x^2 | | -21-18y+y=13 | | e^4x+2e^2x-24=0 | | 1000*q=1.4597 | | log81^1/9=x | | 3*-7-6y+y=13 | | 12p-15+6p=-27 | | 18x=x+y | | 0=-2x^2-10x | | Y=-0.3x-5.3 |